Nightmare frequency and nightmare distress in psychiatric inpatients - Schredl, Michael; Anzenberger, Elisabeth; Schilling, Claudia (European archives of psychiatry and clinical neuroscience, 2024)
Previous research indicated that the prevalence of frequent nightmares and/or the presence of a nightmare disorder is quite high in patients with mental disorders. In the present study, 75 randomly selected psychiatric inpatients were interviewed and completed questionnaires regarding nightmares, sleep, and psychopathology. The percentage of patients with nightmares once per week or more often was 61.54% in the group with PTSD diagnosis (N = 13) and 40.32% in the patients without PTSD diagnosis (N = 62). Moreover, depression scores and having PTSD were related to heightened nightmare distress. Based on the high prevalence rates of frequent nightmares, future research should aim at understanding better the interplay between psychopathology and nightmares and test whether nightmare interventions like Imagery Rehearsal Therapy might be beneficial for patients with mental disorders.